2011
DOI: 10.5732/cjc.011.10050
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy for locally advanced cervical cancer reduces surgical risks and lymph-vascular space involvement

Abstract: Neoadjuvant chemotherapy (NACT), which can reduce the size and therefore increase the resectability of tumors, has recently evolved as a treatment for locally advanced cervical cancer. NACT has been reported to decrease the risk of pathologic factors related to prognosis of cervical cancer. To further assess the effects of NACT on surgery and the pathologic characteristics of cervical cancer, we reviewed 110 cases of locally advanced cervical cancer treated with radical hysterectomy with or without NACT at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In 40 patients undergoing NAC plus radical hysterectomy, median operative time was 260 min and median surgical blood loss was 500 ml, similar to those findings in studies of radical hysterectomy for patients with stage IB2 to IIB with a bulky mass reported by He et al and Wang et al [14, 15]. No serious postoperative complications, such as intestinal obstruction and thrombosis, occurred.…”
Section: Discussionsupporting
confidence: 82%
“…In 40 patients undergoing NAC plus radical hysterectomy, median operative time was 260 min and median surgical blood loss was 500 ml, similar to those findings in studies of radical hysterectomy for patients with stage IB2 to IIB with a bulky mass reported by He et al and Wang et al [14, 15]. No serious postoperative complications, such as intestinal obstruction and thrombosis, occurred.…”
Section: Discussionsupporting
confidence: 82%
“…Sixty-eight patients were administered NAC with a base of platinum and then underwent surgery while the remaining 42 patients underwent surgery directly without NAC intervention. In this study 48 out of 68 (70.6%) patients who had prior NAC intervention had complete or partial remission compared to a much smaller response in patients subjected to operation without NAC treatment (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 54%
“…NAC is also reported to reduce the risk of pathological factors that may be associated with the prognosis for cervical cancer. Wang et al, (2011) cited the review of Guo et al, (2015) in which 110 patients with advanced stage cervical carcinoma underwent a radical hysterectomy with or without NAC. Sixty-eight patients were administered NAC with a base of platinum and then underwent surgery while the remaining 42 patients underwent surgery directly without NAC intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemotherapies developed to improve treatment outcomes of cervical cancer which including neoadjuvant chemotherapy (NACT) before CCRT and radical hysterectomy [5]. The aim of NACT is improve the prognosis of patients with LACC by shrinking the tumor and killing metastatic cells before further treatment; however, there is currently no standard NACT regimen [6]. The safety of paclitaxel plus carboplatin as a NACT has been demonstrated in many studies [7], with its efficacy against cervical squamous cell carcinoma varying from patient to patient.…”
Section: Introductionmentioning
confidence: 99%